The reality of intellectual capital management at the Faculty of Physical Education at Tishreen Universit - alideeb, kholoud nizar (Latakia University Journal -Medical Sciences Series, 2020)
The intellectual capital has become a measure of the organization’s success and its ability to continue and compete in the labor market, and an important variable with a significant impact on the success or failure of the organization, especially the knowledge of it, the fact that educational institutions are the source of knowledge and science has made intellectual capital is a way of value creation and one of the main pillars of contemporary performance evaluation systems and the Faculty of Physical Education is one of the educational institutions that seek to achieve success and excellenc. The research aims to identify the reality of intellectual capital in the Faculty of Physical Education, where the reality was identified by distributing a questionnaire to 40 members of the educational and technical staff, the most important findings are that the management of the college does not take care of the components of intellectual capital in addition to the absence of statistically significant differences between the responses of individuals according to the variables in educational attainment and employment. إن رأس المال الفكري أصبح مقياساً لنجاح المؤسسة وقدرتها على الاستمرار والمنافسة في سوق العمل، ومتغيراً هاماً ذا تأثير كبير على نجاح أو فشل المؤسسة وخاصة المعرفية منها ، وكون المؤسسات التعليمية هي منبع المعرفة والعلم جعل من رأس المال الفكري وسيلة لخلق القيمة وأحد الأركان الرئيسية في نظم تقويم الأداء المعاصر ، وكلية التربية الرياضية إحدى المؤسسات التعليمية التي تسعى إلى تحقيق النجاح والتميز، ويهدف البحث إلى تعرف واقع رأس المال الفكري في كلية التربية الرياضية حيث تم التعرف على الواقع من خلال توزيع استبيان على( 40) فرداً من أعضاء الهيئة التعليمية والفنية والموظفين وأهم النتائج التي تم التوصل اليها أن إدارة الكلية لا تعتني بمكونات رأس المال الفكري فضلاً عن عدم وجود فروق ذات دلالة إحصائياً بين استجابات الأفراد وفقا لمتغيرات التحصيل العلمي والوظيفة.